KERAGAMAN BUDAYA DAN PENGARUH BUDAYA ORGANISASI DI LPP ENTER PANGKALAN BUN - Pebrianto, Marhan; Ahmadi, Ahmadi (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
Cultural diversity in organizations is not only related to demographic diversity, but also includes differences in ways of thinking, experiences, and the values ​​held by individuals. This research uses library-based qualitative research, the research used in writing this article is also sometimes referred to as library research. This literature review refers to the use of media to collect library materials such as books, journals and articles that will help solve research problems. The organizational culture at LPP ENTER has succeeded in creating an inclusive and productive learning environment. By prioritizing the values ​​of inclusion, transformational leadership, teamwork, recognition of achievements, and strong relationships with the community.